Problemas familiares y su influencia en la deserción escolar de un adolescente de 15 años de la Unidad Educativa Urdaneta - Verdezoto Peña, Michael Arnaldo (2021)
This study deals with the issue of family problems and their influence on an adolescent's school dropout. The problems that occur in the context of a dysfunctional family due to economic or partner situations that are happening, these conflicts that are generated cause fights, mistreatment and come to affect the children feeling an emotional state of restlessness, frustration, fear, which affects their academic performance followed by dropping out of school, for this reason the objective of this inquiry process is to determine if family problems influenced the school dropout of an adolescent. To carry out this study, various instruments and techniques were used that are very useful in the field of psychology, developed the sessions and applied the tools, a diagnosis was obtained in accordance with the provisions of the diagnostic criteria of the ICD -10, in addition to establishing a psychotherapeutic plan according to each finding obtained.